Digitalisation and sustainability convergence: leveraging artificial intelligence capabilities to enhance agri-food value chains' sustainability in Africa - David Pooe; Watson Munyanyi (Sustentabilidade em Debate)
The convergence of digitalisation and sustainability offers transformative potential for Africa's agri-food value chains. By employing structural equation modelling, this paper investigates the convergence of digitalisation and sustainability in Africa's agri-food value chains, including the mediating role of agri-food supply chain resilience. The critical role that Artificial Intelligence plays in enhancing food supply chain resilience in Africa is at the core of this study. This study employs a deductive research approach to achieve the research objective, drawing on established theories to guide the development of the conceptual model and hypotheses. The results underline the importance of AI-driven initiatives such as Farmers’ Yield Optimization, Food Retail Demand Prediction, Real-time Data Analysis, and Enhanced Supply Chain Administration in strengthening the resilience of agri-food supply chains. These findings suggest that investing in resilience-building measures can generate long-term benefits for the stability and sustainability of agri-food systems.